The Use of Popliteal and Femoral Blocks for Pedis Amputation in Patient with Congestive Heart Failure Stage III - Bisono, Luwih; Tantri, Aida R; Satoto, Darto (This journal is published by the Department of Anesthesiology and Intensive Therapy of Faculty of Medicine, Public Health and Nursing, in collaboration with the Indonesian Society of Anesthesiology and Intensive Therapy , Yogyakarta Special Region Br, 2016)
The choice of peripheral nerve blocks for lower extremity operation are popliteal and femoral block. But at the special condition, the patient could not be performed with general anesthesia, subarachnoid block or epidural block anesthesia because various of reasons. In consequense, it is needed the other anesthesia technique by different way for lower extremity operation using peripheral nerve block. There are some recognized peripheral nerve blocks with or without ultrasonography guidance. Some of them are femoral block, sciatik/popliteal block, ankle block and psoas block. In this case report, the patient with congestive heart failure stage III and history of pulmonary edema with ejection fraction 23% was performed by lateral popliteal and femoral block usg guided for pedis amputation.